Large-Volume Intrathecal Administrations: Impact on CSF Pressure and Safety Implications - Belov, Vasily; Appleton, Janine; Levin, Stepan; Giffenig, Pilar; Durcanova, Beata; Papisov, Mikhail (Frontiers in Neuroscience, 2021)
The increasing number of studies demonstrates the high potency of the intrathecal (IT) route for the delivery of biopharmaceuticals to the central nervous system (CNS). Our earlier data exhibited that both the infused volume and the infusion rate can regulate the initial disposition of the administered solute within the cerebrospinal fluid (CSF). This disposition is one of key factors in defining the subsequent transport of the solute to its intended target. On the other hand, fast additions of large volumes of liquid to the CSF inevitably raise the CSF pressure (a.k.a. intracranial pressure (ICP)), which may in turn lead to adverse reactions if the physiologically delimited threshold is exceeded. While long-term biological effects of elevated ICP (hydrocephalus) are known, the safety thresholds pertaining to short-term ICP elevations caused by IT administrations have not yet been characterized. This study aimed to investigate the dynamics of ICP in rats and non-human primates (NHPs) with respect to IT infusion rates and volumes. The safety regimes were estimated and analyzed across species to facilitate the development of translational large-volume IT therapies. The data revealed that the addition of a liquid to the CSF raised the ICP in a rate and volume-dependent manner. At low infusion rates (<0.12 ml/min in rats and <2 ml/min in NHPs), NHPs and rats displayed similar tolerance patterns. Specifically, safe accommodations of such added volumes were mainly facilitated by the accelerated pressure-dependent CSF drainage into the blood, with ICPs stabilizing at different levels below the safety threshold of 28±4 mm Hg in rats and 50±5 mm Hg in NHPs. These ICPs were safely tolerated for extended durations (of at least 2-25 min). High infusion rates (including boluses) caused uncompensated exponential ICP elevations rapidly exceeding the safety thresholds. Their tolerance was species-dependent and was facilitated by the compensatory role of the varied components of craniospinal compliance while not excluding the possibility of other contributing factors. In conclusion, large volumes of liquids can safely be delivered via IT routes provided that ICP is monitored as a safety factor and cross-species physiological differences are accounted for.